Revisiting the Relationship between Foreign Direct Investment, Digital Competitiveness, and Economic Growth in Emerging Economies - Ambar Tri Hapsari; Bondan Dwi Hatmoko; Aswin Fitriansyah (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the relationship between Foreign Direct Investment (FDI), digital competitiveness, and economic growth in developing and emerging economies. It addresses the fragmented literature by systematically synthesizing how digital readiness enhances the effectiveness of FDI spillovers in promoting sustainable economic growth. Design/methodology/approach – A scoping review was conducted following the PRISMA-ScR framework. Literature published between 2018 and 2026 was collected from Scopus, Web of Science, and Google Scholar. From 530 initial records, 50 peer-reviewed articles met the inclusion criteria and were analyzed through thematic classification and conceptual synthesis. Findings – The review shows that the FDI–growth relationship has shifted from a capital-driven perspective to a capability-based framework. Digital competitiveness, technological readiness, innovation systems, and absorptive capacity significantly strengthen the impact of FDI by facilitating domestic innovation, productivity improvement, and sustainable economic growth. Originality/Value – This study positions digital competitiveness as a key enabling mechanism within the FDI–growth nexus, integrating two previously fragmented research streams. The findings suggest that policymakers should complement FDI attraction strategies with digital transformation, technological capability development, and institutional strengthening to maximize long-term economic competitiveness.